Evaluation of the Risk of Knee Osteoarthritis and Its Predictive Factors with Emphasis on Physical Activity - Parvaneh Shamsipour-Dehkordi; Marzieh Entezari; Robab Sahaf (مجله پژوهش در علوم توانبخشی, 2017)
Introduction: Designing programs for the prevention of osteoarthritis of the knee requires an understanding of its risk factors. The aim of the present study was to determine the relationship between the risk of knee osteoarthritis among the elderly and age, body mass index (BMI), education, depression, physical activity, and gender of the elderly.